ANALISIS SIKAP KONSUMEN DALAM KONSUMSI BUAH KALENG IMPOR DI KOTA PEKANBARU - Halomoan Halomoan; Novia Dewi; Jumatri Yusri (Fakultas Pertanian, Universitas Riau, 2020)
The purpose of this research is to find out how consumer attitudes in the consumption of canned fruit imports against attributes (packaging, pricing, nutrient content, trademarks). Consumer sampling methods in this research using Random Sampling techniques that respondents who meet in person and buy canned fruit imports in the market in the city of Pekanbaru. Method of data collection is done by way of observation, interviews using questionnaire and documentation. Technique of data analysis used analysis techniques in the theory of reasoned action,namely the model developed by Fishbein. The results showed a model of attitudes and subjective norms model. The attitude of consumers towards the purchase of imported fruit in the city of Pekanbaru is positive with a score of 3,422 and still influenced by price, packaging, trademarks, and content of substance.